Portrait of the Services of The ST. Maria Was Approved to Heaven Malang at the Time of The Covid-19 Pandemic - Emmeria Tarihoran; Erly Lumban Gaol (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The 2019 Corona Virus Disease (Covid-19) pandemic, which was officially declared by the World Health Organization (WHO) on March 11, 2020, has ravaged all patterns of social life throughout the world, including the pattern of Church service. The Parish Church of the Assumption of Mary has also deeply felt the impact of the Covid-19 pandemic on its service to the people. However, various strategies are pursued by taking into account the suggestions and instructions of the local government. This study aims to explore the efforts made in the context of Church service and reflect on the impacts caused by the Covid-19 pandemic on the spiritual life and faith formation of the people. The method used in this study uses a descriptive qualitative approach with data collection techniques through observation and interviews.